Extraction of Rubidium and Cesium Ions by Adsorption–Flotation Separation in Titanosilicate-Hexadecyltrimethylammonium Bromide System - Dezhen Fang; Haining Liu; Xiushen Ye; Yanping Wang; Wenjie Han (Separations, 2025)
This study centers on the adsorption–flotation coupling extraction of rubidium (Rb+) and cesium (Cs+) within a titanium silicate (CTS)–cetyltrimethylammonium bromide (CTAB) system, systematically investigating the impacts of pH, aeration rate, CTAB concentration, and flotation time on the extraction efficiency of these elements. Single-factor experiments revealed that the optimal flotation efficiency was achieved when the pH ranged from 6 to 10, the aeration rate was set at 1000 r/min, the CTAB concentration was 0.2 mmol/L, and the flotation duration was 18 min. Under these conditions, the adsorption capacities for Rb+ and Cs+ were recorded as 128.32 mg/g and 185.47 mg/g, respectively. Employing the response surface optimization method to analyze the interactive effects of these four factors, we found that their order of significance was as follows: pH > aeration rate > CTAB concentration > flotation time. The optimized parameters were determined as pH 8.64, bubble formation rate 1121 r/min, CTAB concentration 0.26 mmol/L, and flotation time 18.47 min. Under these refined conditions, the flotation efficiency for both CTS–Rb and CTS–Cs surpassed any single-factor experiment scenario, with the flotation efficiencies for Rb+ and Cs+ reaching 95.05% and 94.82%, respectively. This methodology effectively extracts Rb+ and Cs+ from low-concentration liquid systems, while addressing the challenges of solid–liquid separation for powdered adsorption materials. It holds significant theoretical and practical reference value for enhancing the separation processes of low-grade valuable components and boosting overall separation performance.